La fonction du droit des obligations - Crépeau, Paul-A. (Assurances, 1985)
The following is the first part of a study on the law of obligations by Pr. Paul-A. Crépeau. The second part will appear in the next issue of our magazine. The author examines the function of conventional and legal obligations, in society and in relation to the training of jurists. Illustrations are drawn from judicial decisions dealing with freedom of contract within the limitations imposed by public order and good morals, the concept of civil liability and the concept of fault.